Unravelling the coupling of surface plasmons in carbon nanotubes by near-field nanoscopy. Issue 29 (21st July 2021) - Tian, Xiaoling; Chen, Runkun; Chen, Jianing
Abstract : We experimentally and theoretically investigated the propagation and subwavelength coupling of surface plasmons in carbon nanotube pairs (CNTPs). We found symmetric and anti-symmetric modes formed by plasmon coupling in CNTPs. Abstract : We experimentally and theoretically investigated the propagation and subwavelength coupling of surface plasmons in carbon nanotube pairs (CNTPs). We found two plasmon modes in the Fourier transformed near-field images of CNTPs, while only one propagating plasmon mode in the single carbon nanotube (CNT). Using the finite element method (FEM), we calculated plasmon coupling between two carbon nanotubes. We attributed the observed two plasmon modes to the symmetric and asymmetric coupling of the plasmons between the two CNTs. Using numerical simulation, we further investigated the plasmon coupling strength and found that it is sensitive to the separating distance of CNTs. When the separation is larger than 5 nm, the plasmon coupling attenuates. We show that near-field optical imaging is a feasible way to characterize the plasmon coupling of CNTs, even if the separation of the CNTs is only a few nanometers.